Surfactant-assisted ammonium vanadium oxide as a superior cathode for calcium-ion batteries - Thuan Ngoc Vo; Kim, Hyeongwoo; Hur, Jaehyun; Choi, Wonchang; Kim, Il Tae (ROYAL SOC CHEMISTRY, 2018)
Ammonium vanadium oxide (NH4V4O10) was adopted as an efficient and high-capacity cathode for Ca-ion batteries. The conventional hydrothermal process allowed an NH4V4O10 cathode to exhibit an initial capacity of 125 mA h g(-1) at 0.1 A g(-1). However, the process led to a size range of hundreds of nanometers to a few microns, which limited the electrochemical performance. Accordingly, we created uniform rod-like NH4V4O10 particles approximately 100 nm in breadth by adding the surfactant sodium dodecylbenzenesulfonate as a soft template during the sample preparation. The addition of the surfactant not only reduced the crystal size but also generated an Na-doping effect; as a result, it increased the proportion of V4+/V5+ active sites. The Na-doped NH4V4O10 electrode delivered an initial capacity of 150 mA h g(-1) and maintained the capacity by demonstrating coulombic efficiencies of 90-95% without notable fading after 100 cycles in a three-electrode system. Moreover, the material produced via the new route required less time to be activated before reaching the highest-capacity state. Ex situ X-ray diffraction analysis indicated the formation of new phases during the migration of Ca ions, and the small change in the lattice plane suggested that NH4V4O10 can exhibit stable electrochemical performance during prolonged cycling. Finally, a full-cell study demonstrated that the Na-doped NH4V4O10 electrode delivered a maximum discharging capacity of 75 mA h g(-1) with both high coulombic efficiency (approximate to 80%) and approximate to 100% capacity retention for 100 cycles.
Keywords: METAL-ORGANIC FRAMEWORKS; HIGH-PERFORMANCE; SODIUM; ELECTRODES; SIZE; INTERCALATION; STORAGE